The Science of Reading in Practice : An Analysis of Instructional Materials for Literacy in Selected States and Municipalities in Brazil - World Bank (Washington, DC, 2022)
The goal of this study is to assess if literacy practices in the highest-performing education systems in Brazil are aligned with the Science of Reading evidence. By doing so, the study aims to provide practical examples of evidence-based literacy instruction that can be helpful for low and middle-income countries. This report is guided by the following questions: What is the degree of structure and detail of skills in the curricula? What skills should be taught and in which order? How do these skills compare with the World Bank’s Early Grade Reading Rainbow model 20? What is the level of guidance offered to teachers on what to teach and how does this guidance appear in the teaching material? How aligned are the curriculum, textbooks, teacher materials, and monitoring tools? The intended audience for this report includes education actors responsible for designing and implementing literacy policies in a governmental position or supporting governments. The report mainly focuses on the structure and alignment of literacy instruction. An evaluation of specific curricular content or the quality of pedagogical resources is beyond the scope of the paper. As previously mentioned, other World Bank reports provide more guidance on the content and high-quality teaching practices. The current report is deliberately descriptive, as it is primarily focused on the structure of literacy instruction, assessing the presence of key elements mentioned in the literature on the science of reading and how different resources are connected in the literacy practices analyzed. It does not quantify how well a certain system is working or make any assessments on how positive or negative a certain practice is. An assessment of the relationship between specific content and structural effectiveness can be better addressed by another type of analysis.